PULPOTOMY IN HUMAN DECIDUOUS TEETH AND BONE MORPHOGENETIC PROTEIN (rhBMP-2) - Bengtson, Antonio Lucindo; Bengtson, Nadya Galvão; Bengtson, Camilla Regina Galvão; Pinheiro, Sérgio Luiz; Guedes-Pinto, Antonio Carlos (Archives of Oral Research, 2008)
OBJECTIVES: Recent studies of pulpotomy and direct pulp capping using bone morphogeneticprotein (BMP) in the teeth of animals have indicated a role for BMP in the induction and biologicalproduction of dentin. The aim of this study was to observe painful reactions and signs of clinicaland radiographic pathological alterations in human deciduous teeth, as well as to histologicallyexamine pulp tissue after the use of recombinant human BMP-2 in a collagen scaffold. MATERIALAND METHOD: Five deciduous teeth for which pulpotomy had been indicated were studied.rhBMP-2 was placed in the pulp chamber of the teeth, and they were then filled using compositeresin. In two teeth that exfoliated, histological examinations were performed. RESULTS: Aftertwelve months, we observed 100% clinical and radiographic success, with no detectableabnormalities. On the histological sections, areas of inflammation, pulp necrosis and internalreabsorption, as well as the formation of tissue resembling osteodentin in the radicular portion,were observed. CONCLUSIONS: It could be concluded that the absence of symptomatologyand clinical and radiographic alterations suggests that rhBMP-2 is a material with inductive propertiesthat should be further investigated for use as an alternative to pulpotomy treatment.